2013
DOI: 10.1002/app.39840
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and 3D formation of PVA and PEO electrospun nanofibers with embedded urea

Abstract: The behavior of electrospun polyvinyl alcohol (PVA) and polyethylene oxide (PEO) nanofibers embedded with urea is studied as a function of various process parameters. Our results show that three‐dimensional nanofiber networks can be obtained when high concentrations of urea in the solution are used during electrospinning. The nanofibers are characterized using both scanning electron microscope (SEM) and Fourier transform infrared spectroscopy (FTIR). The stability of the nanofiber as a function of electric fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…It can be observed that the formed peaks belong to the PVA only with no more bonds formed with CNFs. The observed pattern is the same compared to pure PVA nanofibers and PVA with CNFs at different weight ratios of CNFs [17].…”
Section: Resultssupporting
confidence: 52%
“…It can be observed that the formed peaks belong to the PVA only with no more bonds formed with CNFs. The observed pattern is the same compared to pure PVA nanofibers and PVA with CNFs at different weight ratios of CNFs [17].…”
Section: Resultssupporting
confidence: 52%
“…The running time of electrospinning process per sample is about 30 min. A high voltage is applied to the syringe’s needle; the droplet of polymer solution takes the shape of a cone known as Taylor cone [ 19 ]. Then, a jet is erupted from the cone and is accelerated towards the collector.…”
Section: Methodsmentioning
confidence: 99%
“…The incorporation of the urea into the two types of patches produced, via blend electrospinning and electrospraying increased the average fiber diameter to 455 ± 67 nm and 672 ± 96 nm, respectively for samples with 2% and 5% urea in the PVB blend, and 518 ± 112 nm for PVB membranes with the electrosprayed solution containing 10% of urea (see Figure 1 E). During electrospinning, water from the air could bind to the urea and became entrapped in the fibers, resulting in a larger diameter of manufactured PVB fibers [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the C–H bond was observed at 2750–3000 cm −1 (stretching) and 1300–1500 cm −1 (bending). Urea addition to the polymer led to H–bond formation between the urea and the ether or hydroxyl group, resulting in a reduction in C–H peak intensity [ 35 ]. The representative frequencies of PVB remain at the same wavelengths as for pristine PVB fibers, C–O–C at 1132 cm −1 and C–O at 999 cm −1 .…”
Section: Resultsmentioning
confidence: 99%